Analisis Persepsi Konten Kreator Tentang Fitur Monetisasi Facebook Pro dan Kesesuaian dengan Prinsip Ekonomi Syariah - Erex Yofanra; Supardi Mursalin; Katra Pramadeka (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The purpose of this study is to determine the Perception of Facebook Pro Content Creators towards the Monetization Features provided by Facebook Pro. To determine the suitability of Facebook Pro Content Creators' perceptions and sharia economic principles in the context of monetization on the Facebook Pro platform. Qualitative approach type. The results of the Content Creator Perception study of the Facebook Pro monetization feature are generally positive. This feature provides additional income opportunities that are beneficial, especially for housewives and Facebook Pro users who have monetized by uploading consistent, interesting content that is widely liked by other users. The existence of Monetization Features such as in-stream ads, Reels Ads, Donations, and Bonuses can help improve the welfare of both financial and non-financial creators. Compliance with Sharia Economic Principles, such as fairness, transparency, and benefits, are generally met in the Facebook Pro monetization feature. However, some aspects such as uncertainty in revenue sharing or conditions that are not fully understood by creators need to be improved to be more transparent and in accordance with sharia values.